JUMLAH RELATIF SEL NEUTROFIL (GR-1+) PADA MENCIT (MUS MUSCULUS) TERINFEKSI STAPHYLOCOCCUS AUREUS SETELAH PEMBERIAN EKSTRAK BUAH MENGKUDU (MORINDA CITRIFOLIA L.) - Mufidah, Zumrotul (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
Objective: The aim of this study was to determine the relative number of neutrophil (GR-1+) on miceinfected Staphylococcus aureus after treatment noni (Morinda citrifolia L.) crude extract. Methods: Micewere devided into two group: non-infected and infected. Non infected group was without S.aureus infectionwhereas the infected group was infected with S.aureus. Group contain kontrol, dose 1 (25 mg/kg BW), dose 2(100 mg/kg BW), and dose 3 (300 mg/kg BW). Oral treatment carried out for 20 days in every morning andeach sample was injected with S.aureus at day 21 with 109 cell/mL. Relative number of neutrophil (GR-1+)was measured using the BD FACSCaliburTM Flowcytometer. Data were analyzed by using Analysis ofVarians (p<0,05) and SPSS 16 for windows. Result: The result showed that administration of noni crudeextract was significantly change the relative number of neutrophil (GR-1+). Conclusion: Treatment of noni(M. citrifolia) crude extract could increase relative amount of neutrophil (GR-1+) on infected S.aureus andwithout infected group. That might be caused by active compound on noni crude extract that can influenceactivity of increasing Granulocyte Colony Stimulating Factor (G-CSF) so can increase relative amount ofneutrophil (GR-1+).